Short‐Term Statin Therapy Induces Hepatic Insulin Resistance Through HNF4α/PAQR9/PPM1α Axis Regulated AKT Phosphorylation - Yijun Lin; Shuying Wang; Zixuan Li; Yuling Zhou; Ruiying Wang; Yan Wang; Yan Chen (Advanced Science)
Abstract Statins, the first‐line medication for dyslipidemia, are linked to an increased risk of type 2 diabetes. But exactly how statins cause diabetes is yet unknown. In this study, a developed short‐term statin therapy on hyperlipidemia mice show that hepatic insulin resistance is a cause of statin‐induced diabetes. Statin medication raises the expression of progesterone and adiponectin receptor 9 (PAQR9) in liver, which inhibits insulin signaling through degradation of protein phosphatase, Mg2+/Mn2+ dependent 1 (PPM1α) to activate ERK pathway. STIP1 homology and U‐box containing protein 1 (STUB1) is found to mediate ubiquitination of PPM1α promoted by PAQR9. On the other hand, decreased activity of hepatocyte nuclear factor 4 alpha (HNF4α) seems to be the cause of PAQR9 expression under statin therapy. The interventions on PAQR9, including deletion of PAQR9, caloric restriction and HNF4α activation, are all effective treatments for statin‐induced diabetes, while liver specific over‐expression of PPM1α is another possible tactic. The results reveal the importance of HNF4α‐PAQR9‐STUB1‐PPM1α axis in controlling the statin‐induced hepatic insulin resistance, offering a fresh insight into the molecular mechanisms underlying statin therapy.